Directly measured free and total 25-hydroxyvitamin D levels in relation to metabolic health in multi-ethnic postmenopausal females in Saudi Arabia. Issue 12 (9th December 2021) - Alharazy, Shatha; Robertson, M Denise; Lanham-New, Susan; Naseer, Muhammad Imran; Chaudhary, Adeel G; Alissa, Eman
Abstract : Background: Measurement of free 25-hydroyvitamin D (25(OH)D) status has been suggested as a more representative marker of vitamin D status than that of total 25(OH)D. Previously, free 25(OH)D could only be calculated indirectly; however, a newly developed direct assay for the measurement of free 25(OH)D is now available. The aim of this study therefore was to investigate directly measured total and free vitamin D levels association with metabolic health in postmenopausal healthy women living in Saudi Arabia. Methods: A sample of 302 postmenopausal women aged ≥50 years ( n   = 302) living in Saudi Arabia were recruited in a cross-sectional study design. Blood samples were collected from subjects for measurement of serum levels of total 25(OH)D, directly measured free 25(OH)D, metabolic bone parameters, lipid profile, and other biochemical tests. Results: A positive correlation was found between directly measured free and total 25(OH)D ( r  = 0.64, P< 0.0001). Total but not free 25(OH)D showed significant association with serum intact parathyroid hormone ( P  = 0.004), whilst free 25(OH)D but not total 25(OH)D showed a significant association with total cholesterol and LDL-C ( P  = 0.032 and P  = 0.045, respectively). Conclusions: Free 25(OH)D and total 25(OH)D were found to be consistently correlated but with different associations to metabolic health parameters. Further research is needed to determine which marker of vitamin D status would be the most appropriate in population studies.